Is It Us? Is It Them? Or Is It This Place? Predicting Civility in State Legislatures. Issue 1 (9th March 2022) - Kettler, Jaclyn J.; Fowler, Luke; Witt, Stephanie L.
Abstract: While many scholars and analysts have observed a decline in civility in recent years, there have been few examinations of how political, economic, and institutional structures may partially explain inter-state differences in these trends. We suggest three potential explanations: (1) institutional structures, such as legislative professionalism and gubernatorial power, have created different contexts in which legislators build and maintain inter-personal relationships; (2) partisan competition has led to less bipartisan cooperation and contributed to strained relationships between members of different parties; and, (3) economic inequity and change has contributed to economic anxiety among citizens, contributing to conflict in legislative bodies as elected officials attempt to navigate emerging policy challenges. To test these explanations, we develop an innovative measure of civility using a national survey of lobbyists and a partial Multilevel Regression and Poststratification (MRP) design. Findings suggest that there is some validity to all three explanations, and signifying that civility is at least partially a result of structural issues.